LEGALISASI KEBIJAKAN ABORSI DIATAS 40 HARI SEBAGAI UPAYA PERLINDUNGAN HUKUM TERHADAP KORBAN PERKOSAAN - Ananda Putri Rihenda; Erdiansyah Erdiansyah; Ferawati Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
The act of abortion in the criminal law system in Indonesia is something that isprohibited from being carried out, but this provision can be waived by the provision ofexceptions to the prohibition of abortion for pregnancies resulting from rape and indicationsof medical emergencies stipulated in the latest Criminal Code, Republic of Indonesia LawNumber 36 of 2009 concerning Health, and Government Regulation Number 61 of 2014concerning Reproductive Health. However, in reality, one of the factors hindering theimplementation of the legalization of abortion for rape victims is the 40-day (6 week) time limitwhich is considered too short to qualify for abortion for rape victims. Therefore, the purposeof this study is to find out the urgency of changes regarding the time limit above 40 days forabortions for rape victims and to formulate arrangements for the legalization of abortions forrape victims in the future.This type of research can be classified into normative legal research using secondarydata, carried out by making library materials the main focus based on library research byexamining and citing reference books related to the problem to be studied. For this research,the data source is secondary data consisting of primary legal materials, secondary legalmaterials and tertiary legal materials. In addition, this research uses qualitative data analysisand produces descriptive data using deductive thinking methods.From the research results, there are two main points that can be concluded, first, theurgency to make changes regarding the time limit above 40 days to have an abortion for rapevictims, namely because the time limit given is relatively short, so it is difficult for rape victimsto fulfill these requirements because the victim suffers physical and psychological harm, thenthe process of investigation and proof takes time, not to mention that it will create newproblems in the future, and more rape victims are unable to have legal abortions and have theopportunity to be criminalized. Second, regarding arrangements for the legalization ofabortion for rape victims in the future, changes need to be made, because the currentregulations cannot fully accommodate the existing problems, because the existence of a timelimit will only make it difficult for rape victims and does not provide a way out.Therefore, the time limit for abortion is considered ineffective if it is still enforced as acondition for abortion. The author's suggestions are first, to provide legal protection for rapevictims who wish to have abortions past the time limit so that victims avoid criminal charges.Second, eliminating the existing time limit and equating the time limit for abortion due tomedical emergency indications with the time limit for abortion due to rape, that is, both arenot given a time limitKeywords: Time Limit-Abortion-Rape Victims